Relationship of T regulatory cells content, activity and serum autoantibodies level in patients with systemic lupus erythematosus receiving rituximab - A V Torgashina (Научно-практическая ревматология)
Objective. To reveal changes of CD+CD25+FoxP3+ T-regulatory cells (T-reg) number in pts with systemic lupus erythematosus (SLE) receiving rituximab and to assess relationship T reg content with changes of disease activity and serum autoantibodies level during treatment. Material and methods. 12 pts with definite SLE were included. Pts were examined before treatment, after 1, 3 and 6 months. Besides routine laboratory tests anti-double-stranded DNA antibodies, B lymphocytes and T reg cells number was evaluated with flow-cytometry. SLE activity was assessed with SLEDAI 2K scale. Rituximab 500 mg was administered every week iv during 4 weeks. 4 pts received combined treatment with cyclophosphan. Results. Mean age of pts was 30,5±9,8 years (Me 31 years, varied from 18 to 49 years), disease duration varied from 7 to 148 months. T reg number before treatment was not decreased and did not correlated with anti-DNA antibodies level. T reg markers (Foxp3+, CD25+, CD4+CD25+) changes and values of SLE activity on SLEDAI 2K after the end of treatment correlated with presence of clinical response to treatment with rituximab in 3 months. Binary logistic regression model including 4 above mentioned predictors in total allows predicting correctly clinical response to therapy in 83% of cases. Conclusion. Changes of CD25+, CD4+CD25+, CD4+CD25+FoxP3+ T-cells number immediately after the end of treatment with rituximab correlated with clinical effect of the treatment and determined subsequent response to anti-B cell therapy.